Acute Pancreatitis in Childhood: A 10-Year Experience From A Thai University Surgical Center - Boonthai A. (2023)
Objectives This study aimed to describe etiology, management, and health outcomes of children developing acute pancreatitis at a tertiary Thailand pediatric surgery center. Methods Medical case records of all index cases during 2006-2016 were analyzed and reported. Results There were 42 male and 37 female patients, with a mean (standard deviation) age of 10.4 (4.5) years, included in the study. Medications were the commonest etiology for 39.3% of acute pancreatitis attacks, 11.4% for biliary tract disease cases, and 8% for postinterventional studies. In 30% of cases, no cause(s) was defined. Sixty-two patients (78.5%) had elevated serum lipase on hospital admission, whereas only 30.4% showed a raised amylase. Hospital stay was 15 days (interquartile range, 6-27 days). Two major complications in the series were pseudocysts (8.8%) and necrotizing pancreatitis (7.6%). Etiological factors and/or antibiotics were not directly linked to any specific complications. Seventeen children (22.8%) had 1 recurrent episode of acute pancreatitis documented. Mortality rate in index cases was 28%, with a higher percentage harboring a preexisting illness (34.4% vs 5.6%; P = 0.01) and in male than in female patients (41% vs 14%; P = 0.01). Conclusions Deaths from pediatric acute pancreatitis are more prevalent in male individuals and those with a preexisting illness. Targeted strategies aimed at "highest-risk"patients may potentially offset mortality.